Interprofessional case conference: impact on learner outcomes. Issue 6 (27th January 2018) - Sordahl, Jeffrey; King, India C; Davis, Kyle; Tivis, Rick; Smith, Scott C; Fisher, Amber; Willis, Janet; Gordon, Timothy; Weppner, William G
Abstract: Transition to interprofessional team-based care is a quickly progressing healthcare model and requires changes in medical training approaches. The Department of Veteran Affairs (VA) has taken a lead role in creating such training experiences, one of which is the establishment of multiple Centers of Excellence in Primary Care Education (CoEPCE). These sites are tasked with developing teaching innovations to better facilitate interprofessional team-based care. The patient-aligned care team interprofessional care update (PACT-ICU) is an interprofessional workplace learning activity with the goals of simultaneously addressing educational and patient care needs. Participants of the PACT-ICU included trainees and faculty of a variety of medical disciplines (e.g., internal medicine, psychology, and pharmacy) involved in a training primary care clinic. Two medically complex patients were presented at each PACT-ICU conference with the purpose of creating a plan of care that maintained an interprofessional team-based approach. Following implementation of the PACT-ICU conference intervention, two primary outcomes were assessed. First, self-assessment of PACT-ICU attendee learner outcomes was measured using a brief questionnaire surveying knowledge gain as it related to increase in knowledge of other professions' capabilities, roles, and responsibilities. Secondly, trainee provider behavior change was evaluated by measuring number of "within PACT" consults before and after participating in PACT-ICU. There was a significant positive change in self-assessed knowledge along with an indication of trainee behavioral change, as measured by electronic medical record consult patterns. This study demonstrates that interprofessional case conferences involving trainees and staff from multiple professions can increase awareness of other professions roles in patient care as well as facilitate interprofessional collaboration. Abstract : Medical trainees who participated in an interprofessional case conference demonstrated increased utilization of collaborative team based care.